Regional character of geomagnetic field directional circularity: Holocene Eastern North America - Lund, Steven P. (Frontiers in Earth Science, 2023)
This study characterizes the paleomagnetic secular variation (PSV) in five Holocene records from Eastern North America. We have determined equi-spaced (100-year) declination and inclination time series for the five sites and compared their directional variability. We note ten correlatable features in both inclination and declination, which indicate that these five PSV records all lie within the same PSV region. We focus on clockwise or counter-clockwise looping of paleomagnetic directions (termed circularity) in these PSV records. We have used two techniques to estimate the circularity. We have first calculated the rate and direction of motion in 200-year intervals for each record. We have also looked for discernable looping (full loops down to 1/2 loops) in individual records. We estimate the loop sizes, durations, and circularity direction. We note the same pattern of circularity in both methods. There are seven intervals of alternating circularity in all five sites. They normally agree in timing and direction of circularity. Both methods suggest an alternating, teeter-totter like, behavior to PSV circularity. This teeter-totter behavior is unbalanced with more time spent in clockwise motion than in counter-clockwise motion. The loops have a distribution of sizes and durations with smaller loops being shorter in duration (400-800 years) and bigger loops having longer durations (600-1200 years). The teeter-totter alternation of clockwise versus counterclockwise circularity is distinctive and may be a normal aspect of PSV. The alternation is not consistent with several traditional ideas about fluid flow (drift, whirling motion, simple convection). Recent studies have identified torsional oscillations as a source for both historical short-term (10 0 ) and millennial-scale (10 3 ) secular variation (Bloxham et al., 2002;Dumberry and Bloxham, 2006). Such a pattern of fluid flow might create the alternating teeter-totter-like behavior of circularity that we see. All five PSV records also display five short (<400 years) intervals of higher-amplitude acceleration and faster PSV rates. These features are analogous to geomagnetic jerks in that they are short intervals of anomalous acceleration. Gallet et al. (2003) showed evidence in PSV for similar anomalous acceleration intervals (~10 2 yrs). We think our anomalous intervals are comparable to them.